Caracterização isotópica de vertebrados do Grupo Bauru como subsídio para compreensão de sua paleoecologia - Lima, Thiago Correia (2022)
The incompleteness of the fossil record hinders the inference of evolutionary and ecological rates and patterns. The anatomical-morphological analysis of the hard remains, although extremely important, can be insufficient to conclude about the paleoecology of some specimens and taxa. Therefore, other methodologies were developed to achieve such inferences. Stable isotope analysis has become an increasingly important method for gathering dietary and environmental information from extinct species in terrestrial and aquatic ecosystems. The benefits of such analyses stem from the geochemical fingerprint that an environment leaves in an organism’s bones, teeth, and tissues. The present work carried out a preliminary isotopic characterization of the vertebrate paleofauna of the Bauru Basin, Late Cretaceous of Southeastern Brazil. The unique environmental conditions and biotic composition present in the region at the time led to peculiar ecological interactions when compared to other pene-contemporary deposits worldwide. The fossil record in the main fossiliferous units of the Basin points to an abundance of titanosaur sauropods as the main terrestrial herbivores throughout the Late Cretaceous, from the Santonian (around 85 My) to the Maastrichtian (around 70 My). Regarding the carnivores, a biotic turnover can be noted due to a preponderance of baurusuchid crocodylomorphs in the Santonian-Campanian strata (which corresponds to the Adamantina Formation), to the detriment of abelisaurid theropods, which become common only in the Maastrichtian Marilia Formation. The scarcity of Abelisauridae among terrestrial carnivores in the Adamantina Formation sets it apart from ecosystems throughout the entire southern hemisphere during the Cretaceous, where this group was dominant. The analysis of stable isotopes will complement the knowledge on the ecological relationships among the aforementioned taxa. After an overview of the paleoecology of the main fossiliferous deposits of the Bauru Basin coming from both the literature and the isotopic data generated in this contribution, the disparate fossil record of the two main groups of predators in the Basin was addressed. After evaluating the degree of niche overlap by the isotopic characterization, our results indicate that there was niche partition amongst the two main carnivorous taxa.